Arts Yearbook 4 : America's Leading annual survey of painting and sculpture with a complete directory of Galleries and Museums. - Banham, Reyner; Davis, Stuart; Gilbert, Creighton; Greenberg, Clement; Holty, Carl; Kessler, Charles S.; Kramer, Hilton; Lackner, Stephan; Meier-Graefe, Julius; Werner, Alfred; Von Wiegand, Charmion; Wollheim, Richard (New York : The Art Digest Inc., 1961)
Beck, Rosemarie ; Beckmann, Max ; Bourgeois, Louise ; Brancusi, Constantin ; Cézanne, Paul ; Chamberlain, John ; Cohen, George ; Dickinson, Edwin ; Gechtoff, Sonia ; Greene, Balcomb ; Hatofsky, Julius ; Hunt, Richard ; Ingres, Jean-Auguste-Dominique ; Kerkam, Earl ; King, William ; Kohn, Gabriel ; Lachaise, Gaston ; Lobdell, Frank ; Manet, Edouard ; Mantegna, Andrea ; Meier-Graefe, Julius ; Michelangelo ; Mondriaan, Piet ; Noland, Kenneth ; Pollock, Jackson ; Rosenborg, Ralph ; Rosenthal, Bernard ; Rothko, Mark ; Shoal, Endrayor ; Still, Clyfford ; Terris, Albert ; Turner, J.M.W. ; Yektai, Manoucher ; Zogbaum, Wilfrid
Engels
boek